TEACTIING ENGLISH THROUGH A MOOC? - Umi Rokhyati (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
MOOC, Massive Open Online Courses, is a new trend in teaching and learning English. It is actually an e learning. The teaching is conducted through internet access. Therefore, the teachers and leamers must have access to internet so that MOOC can be implemented. Learning through a MOOC can be very interesting since learners can meet lots of friends to share ideas, to give and get feedback, to learn from others, and to make a reflection too. A MOOC can also encourage learners to be autonomous. What about teaching through a MOOC? Based on the experience in joining a MOOC, it can be concluded that the program must be very well prepared. The very well preparation includes the material for the course and also for the IT. There must be collaboration betrveen creative English teachers and IT experts to design teaching and learning activity through a MOOC. Is it possible to teach English to our students through a MOOC? This paper tries to describe what, how, and why a MOOC is. lt will be continued by analyzing the strengths and weaknesses of using a MOOC in teaching English. The result hopefully can answer the question written as a title of this paper.